Non-lethal heat shock unlocks SOD gene family diversity for enhanced bacterial resistance in Procambarus clarkii - Zhang, Xin; Cai, Xiuhong; Yue, Shirui; Chen, Zhangxuan; Cheng, Lei; Wang, Shunchang (Frontiers in Immunology, 2026)
BackgroundOxidative stress and endoplasmic reticulum stress (ERS) are critical for crustaceans’ stress responses. Genome-wide identification of superoxide dismutase (SOD) genes in Procambarus clarkia is essential for understanding its stress adaptation and aquaculture disease control.MethodsFive PcSOD genes were identified, with analyses of their structure, motif, chromosomal distribution and phylogeny. Their tissue-specific expression, expression under Vibrio parahaemolyticus challenge, correlation with ERS-related genes, and changes in T-AOC/SOD activity were detected, along with the effect of heat shock pretreatment.ResultsPcSOD genes showed structural diversity and tissue specificity, with time-dependent expression under bacterial challenge. Heat shock pretreatment regulated their expression timing and intensity. Significant correlations between PcSOD and ERS genes were observed in hemocytes under NLHS + V. parahaemolyticus treatment, supported by NLHS-induced Hsp70.ConclusionThese findings suggest a potential coordinated SOD-ERS response in P. clarkia, providing insights for aquaculture disease control strategies.